Southern Cross River Agricultural Development Project Preparation report volume 2 Anexes 1-8 - Federal MInistry of Agriculture, Department of Rural Development (Lagos Federal MInistry of Agriculture, Department of Rural Development, 1983)
This report contains, the agricultural developmental proposals of the Cross River State of Nigeria. Agriculture, fishing and livestock production provide a livelihood for about 500,000 farm families throughout the Cross River State of Nigeria. In the project area, over 3.18 million people of 397,000 families equivalent of 70% of the project area population, are engaged in crop production.
lje 12/07/17
Loans
Keywords: Agricultural Development-Nigeria